Secular trends in body weight and length of children aged 0–2 years. Longitudinal study of five consecutive birth cohorts between 1964–2003 from Wrocław, Poland - Borysławski, Krzysztof; Kozieł, Sławomir (Anthropological Review, 2016)
The aim of this work is to evaluate the intensity of possible secular trends among the five subsequent cohorts of Wrocław (Poland) children aged 0, 6, 12 and 24 months. This document describes secular changes in the body length, weight and the Rohrer’s index. Material: Research material represent the longitudinal studies of five consecutive birth cohorts. The first study involved children born during 1963–1965, and the last in 2003–2005. All of the studies were related to the same social group and were conducted using the same methodology. There are differences in the intensity and direction of the secular trends in children depending on their age. In both sexes the body length of newborns kept increasing until the end of the nineties and decreased in the last decade. The body weight did not change during the 40-year period. This suggests an important role of maternal regulator in fetal development and therefore no clear response to external environmental factors. Secular changes such as the body length and weight, which are the most adequate to the economic changes in Poland, were observed in children aged 6 and 12 months. It may be a result of their highest ecosensitivity during this period. However, there have not been any clear trends observed in the 24 months age group. This may be due to the increasing participation of genetic factors in the development of the child.